Trends in ecology: shifts in ecological research themes over the past four decades. Issue 2 (3rd January 2019) - McCallen, Emily; Knott, Jonathan; Nunez‐Mir, Gabriela; Taylor, Benjamin; Jo, Insu; Fei, Songlin
Abstract : As ecology enters a critical era, more comprehensive studies are needed to improve our understanding of the key themes, major trends, and potential gaps within the discipline. However, as the number of published scientific papers continues to grow, tracking the ever‐expanding body of work becomes increasingly challenging. To identify trends in ecological research, we used recently developed machine learning techniques to perform an automated content analysis on over 84, 841 articles published in 33 top‐ranked scientific journals over the past four decades. We detected a clear decline in the relative frequency of classical theoretical research, and increases in data‐intensive research at both micro‐ and macroscales and on anthropogenic themes. Scattered around the periphery of the expanding thematic space, themes such as microbial ecology, genetics, biogeochemistry, and management and policy have all increased in relative frequency. New educational and research frameworks, as well as funding priorities, should incorporate these contemporary themes so that the field of ecology can better address societal challenges.